Listen-and-Answer Technique in Teaching Listening on News Items to Students at MTs Al-Ihsan Lamongan: A Classroom Action Research - Sukron Ma’mun (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2020)
The purpose of this study is to describe the implementation of listen-and-answer technique in teaching listening on news items. This study uses a classroom action research design consisting of two cycles. The subject of this study was junior high school students of MTs Al-Ihsan Tenggulun Solokuro Lamongan. Each cycle consisted of planning, action, observation, and reflection stages. Data collection techniques used are tests, observations, journals, interviews, and documentation. Data analysis was carried out quantitatively and qualitatively. Based on research data analysis, the average score of students' listening skills on news items in pre-liminary, cycle 1, and cycle 2 increased 62.9. In the first cycle the average score of preliminary study was increased 13.3 points or 24.7% with a class average value of 67.2. In the second cycle, the improvement of the average score of the first cycle was 10.6 points or 15.8% with an average value of 77.8. The improvement between preliminary and cycle 2 was 23.9 points or 62.9%. Additionally, the improvement of students listening skills in news items for each cycle was observed to be followed by changes in students positive behavior.